Symplekin, a Constitutive Protein of Karyo- and Cytoplasmic Particles Involved in mRNA Biogenesis in Xenopus laevis Oocytes - Hofmann, Ilse (The American Society for Cell Biology, 2002)
Symplekin is a dual location protein that has been localized to the cytoplasmic plaques of tight junctions but also occurs in the form of interchromatin particles in the karyoplasm. Here we report the identification of two novel and major symplekin-containing protein complexes in both the karyo- and the cytoplasm of Xenopus laevis oocytes. Buffer-extractable fractions from the karyoplasm of stage IV–VI oocytes contain an 11S particle, prepared by immunoselection and sucrose gradient centrifugation, in which symplekin is associated with the subunits of the cleavage and polyadenylation specificity factor (CPSF). Moreover, in immunofluorescence microscopy nuclear symplekin colocalizes with protein CPSF-100 in the “Cajal bodies.” However, symplekin is also found in cytoplasmic extracts of enucleated oocytes and egg extracts, where it occurs in 11S as well as in ca. 65S particles, again in association with CPSF-100. This suggests that, in X. laevis oocytes, symplekin is possibly involved in both processes, 3′-end processing of pre-mRNA in the nucleus and regulated polyadenylation in the cytoplasm. We discuss the possible occurrence of similar symplekin-containing particles involved in mRNA metabolism in the nucleus and cytoplasm of other kinds of cells, also in comparison with the nuclear forms of other dual location proteins in nuclei and cell junctions.